Speculation, liquidity preference, and monetary circulation - Korkut A. Ertürk (Levy Economics Institute of Bard College, 2006)
The sharp exchanges that Keynes had with some of his critics on the loanable funds theory made it harder to appreciate the degree to which his thought was continuous with the tradition of monetary analysis that emanates from Wicksell, of which Keynes's A Treatise on Money was a part. In the aftermath of the General Theory (GT), many of Keynes's insights in the Treatise were lost or abandoned because they no longer fit easily in the truncated theoretical structure he adopted in his latter work. A part of Keynes's analysis in the Treatise which emphasized the importance of financial conditions and asset prices in determining firms' investment decisions was later revived by Minsky, but another part, about the way self-sustained biases in asset price expectations in financial markets exerted their influence over the business cycle, was mainly forgotten. This paper highlights Keynes's early insights on asset price speculation and its link to monetary circulation, at the risk perhaps, of downplaying the importance of the GT.
Keywords: B22; E12; E4; 330; Keynesian Monetary Theory; Liquidity Preference; Wicksell; Minsky; Asset Price Speculation